Epilepsy, Physical Activity and Sports: A Narrative Review (2018)
ABSTRACT: People with epilepsy (PWE) are less physically active compared with the general population. Explanations include prejudice, overprotection, unawareness, stigma, fear of seizure induction and lack of knowledge of health professionals. At present, there is no consensus on the role of exercise in epilepsy. This paper reviews the current evidence surrounding the risks and benefits associated with physical activity (PA) in this group of patients. In the last decade, several publications indicate significant benefits in physiological and psychological health parameters, including mood and cognition, physical conditioning, social interaction, quality of life, as well as potential prevention of seizure presentation. Moreover, experimental studies suggest that PA provides mechanisms of neuronal protection, related to biochemical and structural changes including release of β-endorphins and steroids, which may exert an inhibitory effect on the occurrence of abnormal electrical activity. Epileptic discharges can decrease or disappear during exercise, which may translate into reduced seizure recurrence. In some patients, exercise may precipitate seizures. Available evidence suggests that PA should be encouraged in PWE in order to promote wellbeing and quality of life. There is a need for prospective randomized controlled studies that provide stronger clinical evidence before definitive recommendations can be made.